Genotypes, superantigen gene profiles, and presence of exfoliative toxin genes in clinical methicillin-susceptible Staphylococcus aureus isolates. - van Trijp, M; Melles, D; Snijders, S; Wertheim, H; Verbrugh, H; van Belkum, A; van Wamel, W (2010)
We compared genotype and virulence gene profiles for strains from carriers with autologous invasive infection (n = 56), nasal isolates from matched carriers (n = 108), and invasive strains from noncarriers (n = 34). Superantigen gene profiles and presence of exfoliative toxin genes A and D were associated with clonal complex rather than with invasive disease.